Ofatumumab plus fludarabine and cyclophosphamide in relapsed chronic lymphocytic leukemia: results from the COMPLEMENT 2 trial. Issue 5 (4th May 2017) - Robak, Tadeusz; Warzocha, Krzysztof; Govind Babu, K.; Kulyaba, Yaroslav; Kuliczkowski, Kazimierz; Abdulkadyrov, Kudrat; Loscertales, Javier; Kryachok, Iryna; Kłoczko, Janusz; Rekhtman, Grygoriy; Homenda, Wojciech; Błoński, Jerzy Z.; et al.
Abstract: In this multicenter, open-label, phase III study, patients with relapsed chronic lymphocytic leukemia (CLL) were randomized (1:1) to receive ofatumumab plus fludarabine and cyclophosphamide (OFA + FC) or FC alone; the primary endpoint being progression-free survival (PFS) assessed by an independent review committee (IRC). Between March 2009 and January 2012, 365 patients were randomized (OFA + FC: n  = 183; FC: n  = 182). Median IRC-assessed PFS was 28.9 months with OFA + FC versus 18.8 months with FC (hazard ratio = 0.67; 95% confidence interval, 0.51–0.88; p  = .0032). Grade ≥3 adverse events (≤60 days after last dose) were reported in 134 (74%) OFA + FC-treated patients compared with 123 (69%) FC-treated patients. Of these, neutropenia was the most common (89 [49%] vs. 64 [36%]). OFA + FC improved PFS with manageable safety for patients with relapsed CLL compared with FC alone, thus providing an alternative treatment option for patients with relapsed CLL. Trial registration:www.clinicaltrials.gov (NCT00824265).